Characteristics of Posterior Cerebral Artery Aneurysms: An Angiographic Analysis of 93 Aneurysms in 81 Patients. Issue 2 (8th April 2014) - Goehre, Felix; Jahromi, Behnam Rezai; Hernesniemi, Juha; Elsharkawy, Ahmed; Kivisaari, Riku; von und zu Fraunberg, Mikael; Jääskeläinen, Juha; Lehto, Hanna; Lehecka, Martin
Abstract: BACKGROUND: Posterior cerebral artery (PCA) aneurysms are rare lesions. Because of their low incidence, the individual or institutional experience is usually limited. OBJECTIVE: To identify specific anatomic features related to PCA aneurysms based on the analyses of pretreatment angiograms. METHODS: We performed a detailed angiographic study of 81 patients with a diagnosis of 93 PCA aneurysms. Fifty-three patients underwent computed tomography angiography, 49 underwent digital subtraction angiography, and 6 underwent magnetic resonance angiography. Between 1980 and 2012, a total of 120 patients with 136 PCA aneurysms and 11 352 patients with 16 444 intracranial aneurysms were treated at our institutions. RESULTS: There were 29 ruptured and 64 unruptured PCA aneurysms. The distribution of the aneurysms along the PCA segments was P1 (n = 39; 9 ruptured), P1/P2 junction (n = 25; 9 ruptured), P2 (n = 21; 5 ruptured), and P3 (n = 8; 6 ruptured). The median aneurysm size was 7 mm for the ruptured and 4 mm for the unruptured aneurysms. Saccular aneurysms (n = 69, 74%) had a typical projection for each location: P1 segment, upward (67%); P1/P2 junction, anterior/upward (80%); P2 segment, lateral (67%); and P3 segment, posterior (50%). Multiple aneurysms were seen in 43 patients. PCA aneurysms related to arteriovenous malformations were observed in 10 patients. CONCLUSION: PCA aneurysms are infrequent lesions, often associated with multiple aneurysms and arteriovenous malformations and are fusiform in shape. Most ruptured PCA aneurysms are smaller than 10 mm and usually distally located. At each PCA segment, saccular PCA aneurysms have a typical dome orientation.